Pengaruh Kompetensi Auditor Terhadap Kualitas Audit pada Kantor Akuntan Publik Di Kota Makassar - Sahidah; Rio Januara (Insan Cita Bongaya Research Journal, 2023)
This study aims to examine the effect of competence on audit quality at the public accounting firm in Makassar City. The approach that is used in this thesis is quantitative research. The population in this study is the Public Accounting firm in Makassar city. The sample is 32, and the data were analyzed by using simple linear regression analysis. Based on the analysis, the value of the dependent variable was obtained from the questionnaire by using likert scale The research result shows that the competence does not influence the audit quality significantly.